2015
DOI: 10.1007/s13277-015-4643-0
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol reduces IL-6 and VEGF secretion from co-cultured A549 lung cancer cells and adipose-derived mesenchymal stem cells

Abstract: Stem cell therapies are important treatment methodologies used in many areas of experimental or clinical medicine. In recent studies of cancer models, Mesenchymal stem cells (MSCs) suppressed the growth of cancer cells. However, also in some studies, stem cell treatments have been shown to induce cancer formation, increase tumor volume, induce the formation of new vessels, and lead to cancer invasion. The presence of MSC-secreted cytokines and their effects on cancer cells limits the reliability of MSC-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…VEGF exerts a strong mitogenic effect on endothelial cells and is regarded as a vascular endothelial cell-specific mitogen, inducing the proliferation of vascular endothelial cells and promoting angiogenesis (51). The biological activity of VEGF depends on the expression levels, the distribution of the target cell receptors and its integration with the receptors (52). Previous studies have demonstrated that hypoxia results in the high expression of VEGF, and that the alteration in retinal microvascular permeability in diabetic retinopathy is associated with VEGF (52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF exerts a strong mitogenic effect on endothelial cells and is regarded as a vascular endothelial cell-specific mitogen, inducing the proliferation of vascular endothelial cells and promoting angiogenesis (51). The biological activity of VEGF depends on the expression levels, the distribution of the target cell receptors and its integration with the receptors (52). Previous studies have demonstrated that hypoxia results in the high expression of VEGF, and that the alteration in retinal microvascular permeability in diabetic retinopathy is associated with VEGF (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The biological activity of VEGF depends on the expression levels, the distribution of the target cell receptors and its integration with the receptors (52). Previous studies have demonstrated that hypoxia results in the high expression of VEGF, and that the alteration in retinal microvascular permeability in diabetic retinopathy is associated with VEGF (52,53). In addition, VEGF and the corresponding receptor are integrated, resulting in retinal endothelial cell proliferation, migration and contributing to the formation of new blood vessels which destroy the blood-retina shielding protection in retinal endothelial cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…52 Moreover, the chemopreventive polyphenolic RSV was reported as antiangiogenic factor which reduces VEGF secretion from cocultured A549. 53 Thanks to the synergistic effect of our chemo-herbal combination (PMX-RSV), the developed nanocarriers succeeded to develop additional control for tumor growth. 27 These results were in agreement with CASP-3 level ( Figure 4D) that is activated in the apoptotic cells in which lungs treated with ion-paired PMX-RSV-LCNPs (F10) showed significantly higher active CASP-3 (2.8 ng/g tissue) than those treated with free PMX/RSV (1.9 ng/g tissue) (P,0.05).…”
Section: Tumor Biomarkersmentioning
confidence: 99%
“…RES has been shown to inhibit the secretion of IL-6 and VEGF from A549 lung cancer cells when they were co-cultured with adipose-derived mesenchymal stem cells [72]. …”
Section: Introductionmentioning
confidence: 99%